International business negotiations - Ghauri, Pervez N., 1948-; Usunier, Jean-Claude (International business and management series., 2003)
Today there is hardly any company that can claim that it is not involved in international business (IB). A huge body of literature is available on international business, but there are very few publications on the most important aspect of IB, namely negotiations. The purpose of this book is to enhance our understanding about the impact of culture and communication on international business negotiations. Consequently to explore the problems faced by Western managers while doing business abroad and provide some guidelines for international business negotiations. The book is divided in four parts.